Role of the cholinergic anti-inflammatory pathway in endotoxemia-induced multi-organ damage in the rat - ERCAN, FERİHA; ÇELİK, MEHMETHAN; YÜKSEL, MERAL; ALİCAN, YAŞAR İNCİ (AVES PRESS LTD, 2015)
Objective: To investigate the role of the cholinergic anti-inflammatory pathway and interaction of inducible nitric oxide (iNOS) and cycloxygenase (COX)-2 in organ dysfunction in rat sepsis. Methods: Lipopolysaccharide (LPS) (10 mg/kg; intraperitoneally) was given to Sprague-Dawley rats to induce sepsis. Groups were treated with nicotine alone or with nicotinic receptor antagonist mecamylamine (3 mg/kg; subcutaneously), selective iNOS inhibitor aminoguanidine (8 mg/kg; intraperitoneally) or selective COX-2 inhibitor nimesulide (8 mg/kg; intraperitoneally). Six hours after LPS, liver, kidney and lung samples were obtained for malondialdehyde (MDA), glutathione (GSH), myeloperoxidase (MPO), chemiluminescence assays and microscopic evaluation and blood was obtained for alanine transaminase (ALT), aspartate aminotransferase (AST) and blood urea nitrogen (BUN) assays. Results: Sepsis increased ALT (p<0.05), AST (p<0.01) and BUN (p<0.001), tissue MDA (p<0.01 for liver and p<0.05, for kidney and lung), tissue MPO (p<0.01, for liver; p<0.05, for kidney; p<0.001, for lung) and chemiluminescence (luminol p<0.001, for all tissues; lucigenin p<0.001 for liver and p<0.01 for kidney and lung) while decreasing GSH (p<0.01, for liver and kidney) compared to control. Nicotine prevented the increase in ALT, AST and BUN (p<0.05, for each), increase in liver and renal MDA (p<0.05, for each), consumption of GSH (p<0.01, for liver and kidney), injury score (p<0.05, for liver and kidney) and increased MPO (p<0.05, for liver and p<0.01, for kidney and lung). Beneficial effects of nicotine seemed to persist in the presence of other therapies. Conclusions: Nicotine in sepsis protects the tissues partially via activation of the cholinergic anti-inflammatory pathway independently of the iNOS and COX-2.
Keywords: Sepsis; rat; cholinergic anti-inflammatory pathway; nicotine; inflammation